Helmintos de aves aquáticas (Pelecaniformes: Ardeidae) do sul do Brasil - Bernardon, Fabiana Fedatto (2013)
The Ardeidae family is composed of more than 60 species, being one of the largest and most representative families of birds with characteristics adapted to wetlands. Rio Grande do Sul is characterized by presenting ecosystems which harbor a unique diversity of waders, where there is the record of 13 species of Ardeidae. Due to lack of information on the diversity of helminths in the Ardeidae family in Rio Grande do Sul, the work was developed with the goal of identifying the helminthfauna of nine species of Ardeidae and determine the parameters of prevalence, mean abundance and mean intensity. Were examined 30 birds of the Ardeidae family (Pelecaniformes), Ardea alba , Ardea cocoi, Butorides striata, Bubulcus ibis, Egretta thula, Ixobrychus involucris, Nycticorax nycticorax , Syrigma sibilatrix e Tigrisoma lineatum from the natural environment of the cities of Pelotas, Capão do Leão e Rio Grande, RS, Brazil. The birds were necropsied to collect helminths, prepared in accordance with the protocols used for each group and identified. As a result there was obtained species of Trematoda, Nematoda and Acanthocephala and their parasitological parameters as follow below: Trematoda: Digenea, Amphimerus interruptus (P=3,3%; AM=0,1; IM= 3,0), Apharyngostrigea ardearum (P=40%; AM=18,6; IM= 46,6), Ascocotyle sp. (P=33,3%; AM=88,4; IM= 265,3), Clinostomum complanatum (P=30%; AM=1,1; IM= 3,8), Episthmium proximum (P=23,3%; AM=1,0; IM=4,2), Ithyclinostomum dimorphum (P=6,6%; AM=0,1; IM=2,5), Nephrostomum limai (P=10%; AM= 0,3; IM=3,6), Ribeiroia insignis (P=10%; AM=2,8; IM=28,0 ) and Stomylotrema sp. (P=3,3%; AM=0,03; IM=1,0) belonging to eight families: Nematoda: Contracaecum microcephalum (P=80%; AM=15,1; IM=18,8), Desportesius invaginatus (P=43,3%; AM=2,76; IM=6,3), Desmidocercella ardeae (P=16,6%; AM=1,3; IM=8,0), Eustrongylides sp. (P=13,3%; AM=1,3; IM=10,2) and Baruscapillaria sp. (P=10%; AM=0,5; IM=5,0). Acanthocephala: Acanthocephalus sp. (Echinorhynchidae) (P=3,33%; AM=0,03; IM=1,0), Andracantha sp. (P=33,3%; AM=15,2; IM=45,8), Arhythmorhynchus sp. (P=6,66%; AM=0,16; IM=2,5) and Polymorphus sp. (Plagiorhynchidae) (P=13,3%; AM=1,3; IM=10,2). Tigrisoma lineatum was the only negative for all groups Ixobrychus involucris was negative for the presence of Trematoda and Bubulcus ibis negative for acanthocephalans. The Trematoda, Nematoda and Acanthocephala mentioned above are for the first time recorded in the Ardeidae family in Rio Grande do Sul in Brazil, some of the hosts and their helminth characterizes first occurrence. We have found insulated proglottids of cestodes in small and large intestine in some birds, but could not identify them.